194k views
5 votes
What’s the answer?????

What’s the answer?????-example-1

2 Answers

3 votes

Answer:

p = -3

Explanation:

Add +4 to both sides of the equation to get -2p = 6. Divide both sides by -2. -2/-2 = 1, and 6/-2 = -3. Therefore, p = -3. You can check your work through substitution: -2(-3) - 4 = 2. 6 - 4 = 2.

User Mortehu
by
5.3k points
4 votes

Answer:

p = -3

Explanation:

Solve for p:

-2 p - 4 = 2

Add 4 to both sides:

(4 - 4) - 2 p = 4 + 2

4 - 4 = 0:

-2 p = 2 + 4

2 + 4 = 6:

-2 p = 6

Divide both sides of -2 p = 6 by -2:

(-2 p)/(-2) = 6/(-2)

(-2)/(-2) = 1:

p = 6/(-2)

The gcd of 6 and -2 is 2, so 6/(-2) = (2×3)/(2 (-1)) = 2/2×3/(-1) = 3/(-1):

p = 3/(-1)

Multiply numerator and denominator of 3/(-1) by -1:

Answer: p = -3

User M Nottingham
by
4.8k points